Draft Ninth Five Year Plan (1997-2002) Andhra Pradesh Volume - II (Sectoral Programmes) Irrigation and Flood Control - Planning Commission (Planning Commission, 1997)
Andhra Pradesh State’s economy is mainly dependent on agriculture. The State is rightly called River State as it is blessed with the Major River Systems like Godavari, Krishna, Pennar and 37 other rivers. Thus the State has a vast scope of developing Irrigation Potential. Andhra Pradesh has a mean annual rainfall of 858 mm and about 670 mm i.e. 78% of the total rainfall is contributed by South-West Monsoon and the balance by North-East Monsoon.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh